2017
DOI: 10.21859/hums-24021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Changes in Heart Rate Recovery Before and after Cardiac Rehabilitation in Patients Undergoing the Coronary Artery Bypass Surgery Based on the Risk Factors for Heart Failure, Diabetes and Smoking

Abstract: ‫ـام‬ ‫انجـ‬ ‫ـی‬ ‫زوجـ‬ ‫ـی‬ ‫تـ‬ ‫ـاری‬ ‫آمـ‬ ‫همیــن‬ ‫و‬ 21/01 ± 7/74 ‫بیمــاران‬ ‫میــان‬ ‫در‬ ‫بازتوانــی‬ ‫از‬ ‫قبــل‬ ‫قلــب‬ ‫ضربــان‬ ‫بازیافــت‬ ‫میانگیــن‬ ‫هــا:‬ ‫یافته‬ ‫ـاران‬ ‫بیمـ‬ ‫ـروه‬ ‫گـ‬ ‫در‬ ‫ـب‬ ‫قلـ‬ ‫ـان‬ ‫ضربـ‬ ‫ـت‬ ‫بازیافـ‬ ‫ـن‬ ‫میانگیـ‬ .)P = 0/000( ‫ـود‬ ‫بـ‬ 25/54 ± 7/62 ‫ـی‬ ‫بازتوانـ‬ ‫از‬ ‫ـس‬ ‫پـ‬ ‫ـن‬ ‫میانگیـ‬ ‫در‬ ‫ـود.‬ ‫بـ‬ 25/17 ± 6/59 ‫آن‬ ‫از‬ ‫ـس‬ ‫پـ‬ ‫و‬ ،22/33 ± 7/42 ‫ـی‬ ‫بازتوانـ‬ ‫ـام‬ ‫انجـ‬ ‫از‬ ‫ـل‬ ‫قبـ‬ ‫ـپ‬ ‫چـ‬ ‫ـن‬ ‫بطـ‬ ‫ـال‬ ‫نرمـ‬ ‫ـرد‬ ‫عملکـ‬ ‫… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This is while no significant alternations were observed in resting SBP and DBP in females and males in the control group (p ≥ 0.05). These results agreed with the findings of Yazdi et al 33 who reported positive effects of cardiac rehabilitation programs on the heart rate and blood pressure. In the present study, reduced RPP observed in MI patients after HBCRP was accompanied with improved cardiac functional capacity in both females and males (P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…This is while no significant alternations were observed in resting SBP and DBP in females and males in the control group (p ≥ 0.05). These results agreed with the findings of Yazdi et al 33 who reported positive effects of cardiac rehabilitation programs on the heart rate and blood pressure. In the present study, reduced RPP observed in MI patients after HBCRP was accompanied with improved cardiac functional capacity in both females and males (P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 93%